HUBUNGAN ANTARA PEMANFAATAN E-JOURNAL DAN MOTIVASI BELAJAR DENGAN KEMAMPUAN PENGETAHUAN KEPUSTAKAAN - Astrid Natasya Rachmatia; Khasanah Khasanah (Akademika, 2019)
The research is purposed to examine, 1). A significant relationship between the use of electronic journals and library knowledge, 2). A significant relationship between motivation to learn and library knowledge, 3). A significant relationship between the use of electronic journals and motivation to learn together with library knowledge. The hypothesis of this study is, 1). There is a positive relationship between the use of electronic journals and library knowledge, 2). There is a positive relationship between motivation to learn and library knowledge, 3). There is a positive relationship between the use of electronic journals and motivation to learn together with library knowledge.The result of test showed: 1). The first hypothesis is accepted, there is a positive relationship between the use of electronic journals and library knowledge, 2). The second hypothesis is rejected, because from the test results it can be seen that there is no relationship between motivation to learn and library knowledge, 3). The third hypothesis is accepted, there is a positive relationship between the use of electronic journals and motivation to learn together with library knowledge skills with low coefficient levels.